Variants in CFAP410 cause a range of retinal and skeletal phenotypes - Ryan E. Schmidt; Amy E. Pohodich; David Birch; Kaylie Jones; Byron L. Lam; Emily H. Jung; Nieraj Jain; Michalis Georgiou; Omar A. Mahroo; Andrew R. Webster; Michel Michaelides; Benjamin Bakall; et al. (npj Genomic Medicine)
Abstract Ciliopathies are associated with a range of phenotypes including retinal degeneration and skeletal abnormalities. We present a retrospective study of 49 patients with variants in Cilia and Flagella Associated Protein 410 (CFAP410) from multiple ophthalmic centers across the world. Common clinical features included early-onset reduced visual acuity, photophobia, and delayed light-to-dark adaptation. A cone-rod dystrophy pattern was observed roughly two times more commonly than rod-cone dystrophy. A minority of patients (22.4%) presented with skeletal abnormalities consistent with axial spondylometaphyseal dysplasia (SMDAX). Patients with the most severe ophthalmic and skeletal phenotypes had disease-associated variants within conserved leucine-rich regions of CFAP410, and the structural effects of these variants were modelled using ChimeraX. This report furthers our understanding of CFAP410-associated clinical phenotypes such as retinal dystrophy and skeletal dysplasia.